MoP supported on reduced graphene oxide for high performance electrochemical nitrogen reduction. Issue 4 (8th January 2020) - Zhou, Yan; Yu, Xinping; Sun, Fengchao; Zhang, Jun
Abstract : MoP nanoseeds grown on rGO for high-performance electrocatalytic nitrogen fixation. Abstract : Electrocatalytic nitrogen fixation under ambient temperature and pressure has always been considered crucial in the ammonia industry. In this study, MoP nanoparticles were evenly grown on few-layered reduced graphene oxide (MoP@rGO) and served as an efficient electrocatalyst for NRR. The MoP@rGO electrocatalyst showed an excellent NRR activity with a high average NH3 yield of 7.5 μg h −1 mg −1 cat (at −0.6 V vs. RHE) and high faradaic efficiency of 9.1% (at −0.5 V vs. RHE). The excellent catalytic activity and stability of MoP@rGO originated from the increased rate of electron transfer between MoP and rGO, enlarged active surface area, synergetic effect between MoP and rGO, and excellent chemical stability. This study thus opens an alternative route towards NRR electrocatalysis.